2014
DOI: 10.1163/15685411-00002809
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and basic ecology of Heterodera schachtii and H. betae wild populations developing on sea beet, Beta vulgaris ssp. maritima

Abstract: Most populations of crop pathogens have wild relative populations from which they can originate but for which basic knowledge of their ecological requirements in natura is scarce. However, the study of spatial distribution and ecology of wild pathogen populations may help control them in crops through a better understanding of the environmental factors driving population dynamics.Here, we focused on Heterodera schachtii and H. betae, two cyst nematodes that cause severe damage to sugar beet (Beta vulgaris ssp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
2
8
0
Order By: Relevance
“…A recent study on the spatial distribution of both beet cyst nematodes on sea beet, Beta vulgaris spp. maritima reported that H. schachtii mainly occurred in the colder environments of northern Europe, whereas H. betae was preferentially distributed in the warmer environments of southern Europe (Gracianne et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the spatial distribution of both beet cyst nematodes on sea beet, Beta vulgaris spp. maritima reported that H. schachtii mainly occurred in the colder environments of northern Europe, whereas H. betae was preferentially distributed in the warmer environments of southern Europe (Gracianne et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction, PCR amplification of ITS sequence, and digestion of PCR products were performed as described in Gracianne et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…By multiplying the ratio of H. schachtii among the 40 larvae with the number of cysts we sampled, we estimated the number of H. schachtii cysts contained in our samples. DNA extraction, PCR amplification of ITS sequence, and digestion of PCR products were performed as described in Gracianne et al (2014).…”
Section: Molecular Characterization and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea beets are common along the European Atlantic and Mediterranean coastlines (De Cauwer, Dufay, Cuguen, & Arnaud, 2010;Hautekèete, Piquot, & Van Dijk, 2002). Wild populations of H. schachtii have been found on wild sea beet populations located along the Atlantic coastline from Spain to Denmark (Gracianne et al, 2014). This wide geographical occurrence provides the opportunity to explore the patterns of gene flow over different spatial scales in the wild.…”
Section: Introductionmentioning
confidence: 99%